Integration of the Urea Fertilizer Industry Process Safety Index - Mahfud; Rahman, Chaidir (PT FORMOSA CENDEKIA GLOBAL, 2023)
The chemical industry has different stages of the production process, depending on the materials used and the products produced. Typically, previous approaches only use one or two parameters. The focus of this study is on a safety assessment metric called the Index Process Safety Value (IPSV). The evaluation process using IPSV involves initially identifying parameters, evaluating each parameter using IPSV, and then integrating the assessments. Integration assessments can be used to ascertain the level of risk involved in the standardization process. Standardization is carried out to ensure the specific attributes of each industrial process flow. Where in this standardization there are variations in index values and levels of potential danger. This main and initial process is the core of the Urea production process stages. Of the several stages of the urea production process, the one with the highest level of danger is during the production of Urea in the synthesis process, namely in the Reactor (DC101) with an index value of 0.4, while the lowest is in the urea synthesis process, namely in the Condenser (EA101) with the average index value is 0.28. This IPSV method can be used to analyze process safety, especially for the urea synthesis unit at Factory 5 of PT Pupuk Kaltim